Ventilação mecânica de curta duração com altos níveis de O 2 em pulmões de ratos idosos - Cavassani, Sâmia Santos; Junqueira, Virginia Berlanga Campos; Moraes, Juliana Britto; Luzo, Karen Kristina; Silva, Claudeny Matos Assis; Barros, Maciel; Marinho, Márcia [UNESP]; Simões, Ricardo Santos; Oliveira-Júnior, Itamar Souza (FapUNIFESP (SciELO), 2011)
Purpose: To evaluate the effects of mechanical ventilation (MV) of high-oxygen concentration in pulmonary dysfunction in adult and elderly rats. Methods: Twenty-eight adult (A) and elderly (E), male rats were ventilated for 1 hour (G-AV1 and G-EV1) or for 3 hours (G-AV3 and G-EV3). A and E groups received a tidal volume of 7 mL/kg, a positive end-expiratory pressure of 5 cm H2O, respiratory rate of 70 cycles per minute, and an inspiratory fraction of oxygen of 1. We evaluated total protein content and malondialdehyde in bronchoalveolar lavages (BAL) and performed lung histomorphometrical analyses. Results: In G-EV1 animals, total protein in BAL was higher (33.0±1.9 μg/mL) compared with G-AV1 (23.0±2.0 μg/mL). Upon 180 minutes of MV, malondialdehyde levels increased in elderly (G-EV3) compared with adult (G-AV3) groups. Malondialdehyde and total proteins in BAL after 3 hours of MV were higher in elderly group than in adults. In G-EV3 group we observed alveolar septa dilatation and signifcative increase in neutrofles number in relation to adult group at 60 and 180 minutes on MV. Conclusion: A higher fraction of inspired oxygen in short courses of mechanical ventilation ameliorates the parameters studied in elderly lungs.
Short courses of mechanical ventilation with high-O 2 levels in elderly rat lungs
Keywords: Aging; Lung injury; Neutrophil infiltration; Oxidative stress; Rats; Ventilator-induced lung injury